Joint optimization of power allocation and relay location for regenerative relaying with multi-antenna reception at destination - Zhang, Xiao Juan. (2013)
We consider joint power allocation (PA) and relay positioning in a dual-hop regenerative relay system with multiple antennas equipped at the destination. With a fixed relay location, an adaptive PA strategy at the source and relay under a sum power constraint that minimizes the system outage probability is presented. With a fixed PA strategy, the optimal relay location is derived. We then propose to jointly optimize PA and relay location. It is shown that employing more destination antennas and/or choosing an appropriate relay location can significantly save the power needed at the relay. Numerical results are presented to demonstrate the performance of the proposed PA and relay positioning algorithms.